Subspace Alignment and Separation for Multiple Frequency Estimation - Yu, Runyi; Ince, Erhan A.; Hocanin, Aykut (IEEE-Inst Electrical Electronics Engineers Inc, 2015)
In this letter, a new subspace based estimator that can effectively provide the order and frequencies of multiple sinusoids in noise is proposed. The estimator, referred to as SAS-Est (Subspace Aligning and Separating Estimator), simultaneously seeks to separate the steering vectors from the noise subspace and align them to the signal subspace. The angles between subspaces and the generalized Kullback-Leibler divergence are used in characterizing the alignment and separation. Minimizing the divergence leads to maximal subspace separation and best alignment, thus allowing improved performance. Simulations in additive white Gaussian noise show that the new estimator offers an improvement for both model order and frequency estimation. When compared with other methods, the improvement is more pronounced for high model orders and low signal-to-noise ratio values.
Keywords: Generalized Kullback-Leibler divergence; multiple signal classification (MUSIC); order estimation; parameter estimation; subspace alignment; subspace separation